A PROSPECTIVE STUDY EVALUATING ELECTIVE ORTHOPEDIC OPERATING THEATRE EFFICIENCY AT A SOUTH AFRICAN TERTIARY HOSPITAL - Makanisi, Hylda; Hlongwane, Thenjiwe; Lushiku, Toms; Mogotsi, Kena (Student’s Journal of Health Research Africa, 2024)
Background The demand for elective orthopedic surgery has increased in South Africa due to an increasing burden of trauma and financial constraints caused by a poorly performing economy. This highlights the importance of orthopedic operating theatre (OT) efficiency in this resource-constrained country. This study aimed to assess the efficiency of elective orthopedic operating theatres at a SA tertiary hospital. Methods This was a cross-sectional study of elective orthopaedic OT lists over 8 weeks, at Chris Hani Baragwanath Academic Hospital, SA. Data assessed during the study included sub-specialty, number of scheduled and completed cases, time OT commenced activities, time OT ceased activities, case time, turnover time, raw theatre utilization as well as the day of surgery cancellations. The data was collected using a password-protected REDCap database form and analyzed with descriptive statistics. Results A total of 117 OT lists equating to 342 cases were included from different orthopaedic subspecialities. The total available OT time was 58331 minutes, of which a large majority, 46638 minutes (80%), was used as case time during conventional OT working hours (95.4%). Fifty-three percent of OT lists started early, whereas 29.9% started late; 65% of them were underran and 30% overran. The mean turnover and first-case starting times delays were 39 minutes and 7.1 minutes, respectively. The overall raw theatre utilization was 83.0% (range: 71.8-88.2%, SD 16.3) with a DOSC (day of surgery cancellation) rate of 19%. Conclusion Overall, elective orthopedic OT utilization was efficient at CHBAH. The challenge posed by cancelled surgeries in CHBAH must be addressed as facility-related reasons were cited as the main reason for cancellations. This will further improve the orthopedic OT efficiency in this hospital. Recommendation Optimizing preoperative patient assessment and preparation to identify cases that could lead to DOSC